2009
DOI: 10.1002/hep.23428
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-inducible gene-6 is a negative regulator of epidermal growth factor receptor signaling in hepatocytes and human hepatocellular carcinoma

Abstract: The mitogen-inducible gene-6 (mig-6) is a multi-adaptor protein implicated in the regulation of the HER family of receptor tyrosine kinases. We have reported recently that mig-6 is a negative regulator of epidermal growth factor receptor (EGFR)-dependent skin morphogenesis and tumor formation in vivo. In the liver, ablation of mig-6 leads to an increase in EGFR protein levels, suggesting that mig-6 is a negative regulator of EGFR function. In line with this observation, primary hepatocytes isolated from mig-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 26 publications
1
69
1
Order By: Relevance
“…that in control littermates. This is correlated with increased EGFR levels and enhanced EGFR signalling in Errfi1 -/-hepatocytes (Reschke et al, 2010) and is consistent with the slower liver regeneration observed in mice carrying liver-specific Egfr ablation .…”
Section: Box 2 Inducible Feedback Inhibitors As Gatekeepers Of Egfr supporting
confidence: 83%
See 2 more Smart Citations
“…that in control littermates. This is correlated with increased EGFR levels and enhanced EGFR signalling in Errfi1 -/-hepatocytes (Reschke et al, 2010) and is consistent with the slower liver regeneration observed in mice carrying liver-specific Egfr ablation .…”
Section: Box 2 Inducible Feedback Inhibitors As Gatekeepers Of Egfr supporting
confidence: 83%
“…EGFR IFIs are expected to provide a key balance to these positive feedback loops, because (i) LRIG1, SOCS4 and/or SOCS5 might promote ligand-independent EGFR degradation; (ii) RALT inhibits EGFR catalytic function regardless of the activating ligand (Anastasi et al, 2007); and (iii) LRIG1, SOCS4, SOCS5 and RALT antagonise the activity of all ErbB family members, including ERBB2, which acts as a signal amplifier. Consistent with this view, levels of EGFR ligands, such as heparin-binding EGF-like growth factor (HB-EGF), which activates both EGFR and ErbB4, and amphiregulin, which stimulates EGFR without inducing receptor degradation, are increased in the lung and liver of Errfi1 -/-mice (Reschke et al, 2010;Jin et al, 2009), which might be regarded as both a consequence and cause of the unabated EGFR activity generated by unbalanced feedback control. that in control littermates.…”
Section: Box 2 Inducible Feedback Inhibitors As Gatekeepers Of Egfr mentioning
confidence: 84%
See 1 more Smart Citation
“…In papillary thyroid cancer, tumor size was inversely correlated with Mig-6 expression (21). In immunohistochemical analysis using a tissue microarray of 111 liver cancer patients, Reschke et al found that Mig-6 expression was barely detectable in the majority of analyzed tumors (64%) (22). We previously demonstrated that Mig-6 expression was downregulated or absent in NSCLC (14).…”
Section: Discussionmentioning
confidence: 84%
“…Downregulation of Mig-6 promotes proliferation and invasion in glioblastoma multiforme (GBM) and PTC cell lines (21,24). Mig-6 is also an endogenous inhibitor of EGF-induced cell migration in human live cancer cell line HepG2 (22). Our previous study showed that Mig-6 specific siRNA promotes proliferation and invasion of H1299 and BE1 cells.…”
Section: Discussionmentioning
confidence: 99%